Adaptasi kurikulum pendidikan anak usia dini di masa pandemi Covid-19 - Megandarisari Megandarisari (Inovasi Kurikulum, 2021)
Covid-19 has an impact on various fields and aspects of human life, including education. Early Childhood Education that implements the learning from home’s system, need to adapt to the curriculum. This study aims to describe the process of adapting the early childhood education curriculum in various aspects, such as: the challenges faced by the parties involved in the process, as well as alternative solutions to overcome various existing obstacles. The research approach used is qualitative research, with literature study method. The conclusion of this research is in the curriculum in special conditions for Early Childhood Education that has been designed by the Ministry of Education and Culture, several things are explained related to curriculum implementation, learning principles, and also learning assessments during the pandemic. Curriculum implementation in special conditions could be implemented optimally when the peoples involved in implementation were able to collaborating well, including school managers, teachers, students, and parents who accompany children to study at home.   Abstrak Covid-19 memberikan dampak pada berbagai bidang dan aspek kehidupan manusia, termasuk pendidikan. Pendidikan Anak Usia Dini yang menerapkan sistem belajar dari rumah, tentu harus melakukan adaptasi pada kurikulum pembelajaran. Artikel ini bertujuan untuk memaparkan bagaimana proses adaptasi kurikulum pendidikan anak usia dini pada berbagai aspek, berikut dengan tantangan yang dihadapi oleh pihak-pihak yang terlibat dalam prosesnya, serta solusi alternatif untuk mengatasi berbagai hambatan yang ada. Pendekatan penelitian yang digunakan yakni penelitian kualitatif, dengan metode studi literatur. Dari hasil pengolahan data, dapat disimpulkan bahwa dalam kurikulum pada kondisi khusus untuk Pendidikan Anak Usia Dini yang telah dirancang oleh Kemendikbud, dijelaskan beberapa hal terkait pelaksanaan kurikulum, prinsip pembelajaran, sampai kepada asesmen pembelajaran di masa pandemi. Implementasi kurikulum pada kondisi khusus dapat berjalan secara optimal dengan adanya kerja sama yang baik antara para pihak yang terlibat dalam implementasi, antara lain pengelola sekolah, guru, peserta didik, serta orang tua yang mendampingi anak belajar di rumah. Kata kunci: Kurikulum, Pendidikan Anak Usia Dini, Pandemi Covid-19